Carbon footprint of different recovery options for the repulping reject from liquid packaging board waste treatment process. (December 2021) - Khan, Md.Musharof Hussain; Laitinen, Vilma; Havukainen, Jouni; Horttanainen, Mika
Highlights: LCA on recovery options for repulping reject from liquid packaging board treatment was conducted. The GWP impact of repulping rejects incineration was identified. The GWP impact from mechanical recycling of repulping reject was investigated. The GWP impact from chemical recycling (pyrolysis) of repulping reject was analysed. Abstract: Liquid packaging board (LPB) is an integral part of storing and transporting liquid food. In addition to its significant advantages, LPB has been challenging the existing waste management sector since its introduction into the market. In most European countries, LPB waste is either incinerated or recycled in the recycling facilities where fibre is recycled, and the repulping reject is separated for incineration. Mechanical recycling and chemical recycling processes are other options for repulping reject treatment. This study used life cycle assessment (LCA) to compare the environmental impacts of three treatment processes, incineration, mechanical recycling and chemical recycling; each was considered with the functional unit of 1 tonne of repulping reject. Furthermore, two sub-scenarios based on the substituted heat produced by energy from the treatment processes were considered. In substituting biomass-based heat sources, chemical recycling generated the lowest greenhouse gas (GHG) emissions, about 560 kg CO2 eq. tonne -1 repulping rejects, followed by the mechanical recycling process (approximately 740 kg CO2 eq. tonne -1 repulping reject). The maximum amount of GHG was emitted from the incineration scenario, which was about 1900 kg CO2 eq. tonne -1 repulping rejects. By substituting natural gas-based heat sources, chemical recycling generated about 290 kg CO2 eq. tonne -1 repulping rejects. On the contrary, the mechanical recycling process generated about 430 kg CO2 eq. tonne -1 repulping rejects and incineration process generated 960 kg CO2 eq. tonne -1 repulping rejects. Uncertainty analysis showed that some assumptions significantly impact the results; however, the chemical recycling process had the lowest environmental impact in almost all uncertainty analysis.